Multilayer Strip Dipole Antenna Using Stacking Technique and Its Application for Curved Surface - Charinsak Saetiaw; Chanchai Thongsopa (International Journal of Antennas and Propagation)
This paper presents the design of multilayer strip dipole antenna by stacking a flexible copper-clad laminate utilized for curved surface on the cylindrical objects. The designed antenna will reduce the effects of curving based on relative lengths that are changed in each stacking flexible copper-clad laminate layer. Curving is different from each layer of the antenna, so the resonance frequency that resulted from an extended antenna provides better frequency response stability compared to modern antenna when it is curved or attached to cylindrical objects. The frequency of multilayer antenna is designed at 920 MHz for UHF RFID applications.